Morphological notes on Gazoryctra sciophanes (Ferguson) and G. confusus (Edwards) (Lepidoptera: Hepialoidea: Hepialidae) - Grehan, John R.; Mielke, Carlos G.c. (Zootaxa, 2020)
The genus Gazoryctra Hübner comprises 10 species in North America and four in northern Eurasia. The remaining diversity of North American Hepialidae is represented by four species of Sthenopis Packard, three species of Phymatopus Wallengren, and one species of Korscheltellus Börner (Nielsen et al. 2000; Grehan & Knyazev 2019). The North American distribution of Gazoryctra extends between Alaska and southern Appalachians and southern Rocky Mountains (Grehan & Mielke 2018). As with other North American Hepialidae, Gazoryctra is absent from much of the southern-central United States where there is ostensibly suitable habitat present as this genus is found in forested regions where it is believed to feed on roots or other organic matter (Schweitzer et al. 2011). This absence may be due to the lack of colonization following regression of inland seas that covered much of this region until the end of the Mesozoic (Grehan & Mielke 2018).